Influences of peers, teachers, and climate on students' willingness to intervene when witnessing anti‐transgender harassment. Issue 6 (15th July 2014) - Wernick, Laura J.; Kulick, Alex; Inglehart, M.H.
ABSTRACT: Transgender young people are at increased risk for bullying, harassment, and negative mental health and academic outcomes compared to the general population as well as compared to other members of lesbian, gay, bisexual, transgender, queer, questioning, and similarly identified (LGBTQQ) communities. To inform interventions to support transgender students, the present study investigates students' willingness to intervene when witnessing anti‐transgender harassment, using data collected from a participatory action research project investigating school climate. Multi‐step linear regression was used to test the impacts of hearing transphobic language and witnessing teachers and others students intervene, while controlling for demographics and school. Hostile climate negatively predicted intervention intentions while witnessing peer intervention positively predicted likelihood to intervene. Witnessing teacher intervention did not significantly predict the outcome. These findings suggest that youth‐led interventions in peer networks might be effective in diminishing transphobic bullying and supporting the healthy development of transgender young people.